Impaired left ventricular stroke volume reserve during clinical dobutamine stress predicts future episodes of pulmonary edema. - Charoenpanichkit, C; Little, W; Mandapaka, S; Dall'Armellina, E; Morgan, T; Hamilton, C; Hundley, W (2011)
OBJECTIVES: The purpose of this study was to determine whether dobutamine-induced abnormal stress changes in left ventricular stroke volume (LVSV) and aortic stiffness predict future pulmonary edema. BACKGROUND: Increased aortic stiffness that decreases LVSV during adrenergic stress may serve as a marker for future pulmonary edema (PE). METHODS: We measured LVSV, ventriculovascular stiffness (pulse pressure/LVSV(index)), and aortic distensibility at rest and during intravenous dobutamine administration using cardiovascular magnetic resonance. Personnel blinded to dobutamine cardiovascular magnetic resonance followed participants longitudinally over time to identify those admitted to the hospital with PE. Data for 44 participants who had a hospital admission for PE were compared with data for 72 participants of similar age, sex, and resting left ventricular ejection fraction who remained PE free. RESULTS: Expressed as median and interquartile range, participants with and without PE exhibited a decreased stress/rest LVSV ratio (0.9 [range 0.7 to 1.1] vs. 1.0 [range 0.9 to 1.2], respectively; p = 0.002), an increased ventriculovascular stiffness stress/rest ratio (1.4 [range 1.0 to 1.6] vs. 1.0 [range 0.8 to 1.3], respectively; p ≤ 0.001); and a decreased stress-induced measure of aortic distensibility (0.8 mm Hg(-3) [range 0.3 to 1.3 mm Hg(-3)] vs. 1.6 mm Hg(-3) [range 1.2 to 3.2 mm Hg(-3)], respectively; p = 0.002). After accounting for age, sex, left ventricular ejection fraction, risk factors for PE, and the presence of dobutamine-induced ischemia, LVSV reserve and the stress/rest ventriculovascular stiffness ratio still differed (p < 0.008 for both) in those with and without PE. CONCLUSIONS: In patients without inducible ischemia during dobutamine stress testing in whom one might otherwise assume a favorable prognosis, the failure to increase LVSV or an increase in ventriculovascular stiffness indicates patients at risk of subsequent PE.